Development of Methods for Calculating the Environmental and Economic Efficiency of Waste Treatment Technologies - KEZEMBAYEVA, Gulmira B. (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.v9.7(31).25, 2019)
Lack of land, transportation costs, environmental hazards, loss of valuable components contribute to the use of new methods for recycling. Therefore, the main objective of the work is to develop a methodology for calculating the environmental and economic efficiency of waste treatment technologies. In the work, economic efficiency was defined as the difference between the profit and costs associated with the implementation and implementation of this technology. The basis of the study, the authors took organic waste farms. As a processing technology, multiphase anaerobic fermentation was taken. It is established that the use of this technology contributes to the production of environmentally friendly bio-fertilizers, biologically active solution and biogas. It is determined that the submitted projects are cost-effective. Because it helps to reduce payments for waste disposal and prevent damage to the environment. Also, the use of biomass energy in the agro-industrial complex will provide an additional source of energy based on local renewable raw materials, concentrated organic fertilizers, bioactive solution.